Exploring the Impact of Personal and Administrative issues Faced by Female Students on Satisfaction Levels with Hostel Facilities and their Influence on Lifestyle: A Statistical Investigation - Yousfani, Kinza; Haider, Bushra; Qureshi, Moiz; Ishaq, Khushboo (Pakistan Journal of Humanities and Social Sciences, 2024)
A hostel is a type of housing that provides shared living spaces for travelers and students, particularly offered by educational institutions where students share their living space. This study aims to evaluate the challenges faced by female students living in university hostels and the impact of these issues on their academic performance. Additionally, it identifies common problems such as satisfaction with hostel facilities, security, and how the hostel environment influences their lifestyle. The population for this study includes all female students residing in Peshawar University hostels. Information was obtained from the Provost's office of the University of Peshawar, showing a total of 1951 female students residing in various hostels during the 2015-16 session across all academic programs with an age range of twenty to twenty-five years. An open-ended questionnaire was developed for in-depth interviews, and various statistical tests were employed in this study. The chi-square test of independence was used to examine associations among different factors, revealing significant associations in most cases. The odds ratio was applied to assess the strength of these associations, uncovering a strong correlation between students' health and the type of food provided by the hostel mess. Additionally, a strong association was found between students' academic performance and group discussions. ANOVA was used to analyze the number of girls in the hostel rooms, leading to the rejection of the null hypothesis. To determine student satisfaction with hostel facilities, a logistic regression model was employed. The results highlighted significant factors such as the name of the hostel, education level, water issues, generator availability, toilet conditions, hostel environment, room accommodation, health facilities, mess condition, academic performance, TV availability, internet access, and good security. Consequently, the study's findings can help improve the quality of hostel services in Pakistan, potentially increasing students' satisfaction with hostel life.